2009
DOI: 10.1002/kin.20428
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polyetherols with isocyanuric ring. Kinetics and mechanisms of reactions, part 1: Reaction between isocyanuric acid and ethylene carbonate

Abstract: The reaction between isocyanuric acid and ethylene carbonate results in the formation of polyetherols. The kinetic and mechanistic studies revealed that the initial step of the reaction is zero order related to ethylene carbonate. The rate-limiting step is the decomposition of an intermediating dianion of ethylene dicarbonate into ethane-1,2-diolate dianion and carbon dioxide. Imide groups of isocyanuric acid inhibit the reaction. The mechanism of reaction was confirmed by spectroscopic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The n = 0 has been found for EC, similarly as for the reaction between EC and IA (cf. part 1 [1]). Thus…”
Section: Kinetics and Mechanism Of Reaction Between Thei And Ecmentioning
confidence: 95%
See 2 more Smart Citations
“…The n = 0 has been found for EC, similarly as for the reaction between EC and IA (cf. part 1 [1]). Thus…”
Section: Kinetics and Mechanism Of Reaction Between Thei And Ecmentioning
confidence: 95%
“…As stated in part 1 [1], the initial stages of the reaction could not be followed by determination of AN, which became almost invariable. Here we have found that upon reaction of EC with the second intermediate (III) the decrease of AN occurred; therefore, the rate of reaction could be determined by AN resulting in calculation of both imide groups of IA and carbonate groups of EC.…”
Section: Analysis Of Reaction Between Intermediates With Ecmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition to their application, the reaction kinetics of hydroxyl compounds with isocyanates has been widely investigated [3,4]. Many factors affect the reaction, such as reactant [5][6][7][8], catalyst [9][10][11][12][13], and solvent [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The literature data do not describe the kinetics and mechanisms of the reactions between alkylene carbonates and IA. In 9,10, the kinetics and mechanism of reaction between EC and IA or 1,3,5‐tris(2‐hydroxyetyl) isocyanurate (THEI, I, where x = y = z =1) in DMSO solvent in the presence of K 2 CO 3 have been presented. The following kinetic law describes the reaction between IA and EC in the presence of this catalyst: V = k 0 ′′ · c K 1/3 · c AH −1 , where c K and c AH are the concentration of catalyst and imide groups of IA, respectively, in mol/kg DMSO.…”
Section: Introductionmentioning
confidence: 99%